Evolution and stages of China's economic inequality from 1978 to 2018. - Yuanzhi Guo (PLoS ONE, 2023)
Regional economic inequality has long been a prominent problem in China's national economic and social development. In this study, the centre of gravity (CG) model is employed to reveal the spatiotemporal patterns and stages of China's economic inequality in 1978-2018, and the characteristics of different stages are explored. The results show that China's economy achieved rapid growth at an average annual growth rate of 9.4% in 1978-2018. Due to the spatial heterogeneity of the location and the unbalanced development strategy, there was a significant economic gradient between eastern and western China. Spatially, there was a notable increase in the agglomeration of GDP and the added value of the three industries, and their CGs moved southwestward as a whole. According to the evolution of regional differentiation characteristics, combined with key historical events, China's economic inequality from 1978 to 2018 could be divided into four stages, i.e., the stages of economic inequality led by institutional reform (1978-1991), market mechanisms (1992-2003), regional coordination (2004-2012), and socioeconomic transformation (2013-2018). The alternation of these four stages reflects how to scientifically deal with the relationship between efficiency and equity in economic development.